Experimental Investigation of Wall Confluent Jets on Transparent Large-Space Building Envelopes: Part 1—Application in Heating Greenhouses - Gasper Choonya; Alan Kabanshi; Bahram Moshfegh (Energies)
Insulating building envelopes is crucial for maintaining indoor thermal comfort, particularly in large-space enclosures like greenhouses having transparent envelopes. Transparent envelopes allow natural light but challenge temperature regulation due to their low thermal mass and high U-values, which enable significant heat transfer between indoor and outdoor environments. This field study aims to experimentally investigate whether warm wall confluent jets (WCJs) can maintain the required indoor climate conditions in a greenhouse exposed to dynamic meteorological conditions in winter. It analyzed the impact of the airflow rate, number of nozzle rows, and room air temperature setpoint on WCJ heating performance on the ceiling, external wall, and room air. Measurements were performed with thermocouples and constant current anemometers, and the response surface methodology evaluated the effect of design variables on WCJ flow, thermal behavior, and the indoor environment. The results show that WCJs provided recommended air velocities and temperatures indoors, with the airflow rate having the strongest effect on flow and thermal behavior, while the number of nozzle rows had a moderate effect. This study developed response surface models related to room air temperature, ceiling surface temperature, external wall temperature, and supply air temperature. Supply temperatures between 27 °C and 40 °C suggest using low-exergy heat sources, like industrial waste heat, to sustain greenhouse operations during winter.